Six year experience of transvenous left ventricular lead implantation for permanent biventricular pacing in patients with advanced heart failure: technical aspects. Issue 4 (1st October 2001) - Alonso, C; Leclercq, C; d'Allonnes, F Revault; Pavin, D; Victor, F; Mabo, P; Daubert, J-C
Abstract : BACKGROUND: Biventricular pacing has been proposed as an adjuvant to optimal medical treatment in patients with drug refractory heart failure caused by chronic left ventricular systolic dysfunction and intraventricular conduction delay. OBJECTIVE: To assess the technical feasibility and long term results (over six years) of transverse left ventricular pacing with the lead inserted into a tributary vein of the coronary sinus. SUBJECTS: From August 1994 to February 2000, left ventricular lead implantation was attempted in 116 patients who were eligible for biventricular pacing (mean (SD) age 67 (9) years, New York Heart Association (NYHA) functional class III/IV, left ventricular ejection fraction 22 (6)%, QRS duration 185 (26) ms). RESULTS: The overall implantation success rate was 88% (n = 102). A learning curve was indicated by a progressive increase in success from 61% early on to 98% in the last year. The mean pacing threshold was 1.1 (0.7) V/0.5 ms at the time of implantation and increased slightly up to 1.9 (0.9) V/0.5 ms at the end of the follow up period (15 (13) months). The rate of acute and delayed left ventricular lead dislodgement decreased from 30% in the early years to 11% after 1999. During follow up, 19 patients required reoperation for delayed lead dislodgement or increase in left ventricular pacing threshold (n = 15), phrenic nerve stimulation (n = 3), or infection (n = 3). CONCLUSIONS: Transverse left ventricular pacing through the coronary sinus is feasible and safe. The rate of implantation failure and of lead related problems has decreased greatly with increasing experience and with improvements in the equipment.